2006
DOI: 10.1088/1009-9271/6/5/06
|View full text |Cite
|
Sign up to set email alerts
|

Tail Emission from a Ring-like Jet: Its Application to Shallow Decays of Early Afterglows and GRB 050709

Abstract: Similar to the pulsar, the magnetic axis and the spin axis of the gamma-ray burst source may not lie on the same line. This may cause a ring-like jet due to collimation of the precessing magnetic axis. We analyze the tail emission from such a jet, and find that it has a shallow decay phase with temporal index equal to −1/2 if the Lorentz factor of the ejecta is not very high. This phase is consistent with the shallow decay phase of some early X-ray afterglow detected by swift. The ring-like jet has a tail cusp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…A ring-shaped jet can be produced by the central engine during the prompt GRB phase. The most natural mechanism may be via precessing (Fargion & Grossi 2006;Zou & Dai 2006). In almost all GRB progenitor models, the central engine is a rapidly rotating compact objects, such as a black hole or a neutron star.…”
Section: Ring-shaped Jetmentioning
confidence: 99%
“…A ring-shaped jet can be produced by the central engine during the prompt GRB phase. The most natural mechanism may be via precessing (Fargion & Grossi 2006;Zou & Dai 2006). In almost all GRB progenitor models, the central engine is a rapidly rotating compact objects, such as a black hole or a neutron star.…”
Section: Ring-shaped Jetmentioning
confidence: 99%
“…However, it fails to describe the jet structure for the situation with θpre = 10 • . The energy distribution in the situation of θopen < θpre is a ring-shaped jet, but not a uniform ring-shaped jet(Granot 2005;Zou & Dai 2006;0 Xu, Huang, & Kong 2008;Xu & Huang 2010).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8]). For the shallow decay phase, Nousek et al [1] and Zhang et al [3] supposed that they come from late energy re-injection; Toma et al [4] proposed a special jet profile; Zou and Dai [7] and Xu and Huang [9] thought that they may be tail emissions from a slow ring-like jet; Fan and Piran [10] and Kong et al [11] considered the possibility of tuning the microphysical parameters; Toma et al [4] suggested that summation of many different directed mini-jets may produce shallow decay radiation; Ghisellini et al [12] suggested a late internal shock emission model; Yamazaki 2009 [13] and Liang et al [14] suggested that by shifting the starting time to ∼10 3 s ahead, the shallow decay becomes normal decay automatically. In this Letter we propose an alternative explanation, that the external shock (in a wind environment) [15−18] before the deceleration time produces the shallow decay phase of early x-ray emission.…”
mentioning
confidence: 99%